1998
DOI: 10.1161/01.str.29.8.1544
|View full text |Cite
|
Sign up to set email alerts
|

Early Intravenous Thrombolysis for Acute Ischemic Stroke in a Community-Based Approach

Abstract: Thrombolysis with rtPA was effectively applied in routine management of stroke patients in a community-based approach with acceptable efforts and without additional costs. Under these circumstances, outcome and complication rates were comparable to those of multicenter trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
133
3
14

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(168 citation statements)
references
References 27 publications
18
133
3
14
Order By: Relevance
“…We found no difference in the occurrence of SICH and early in-hospital mortality between the sub-3 h and 3-4.5 h groups. We observed a similar incidence of SICH (5.7%) and early in-hospital mortality (9.7%) in thrombolysis up to 4.5 h as were reported in the NINDS study [1] and other t-PA registries [7,[12][13][14][15][16][17][18][19], where most patients were treated within 3 h. In the ATLANTIS trial [4], 7.0% of the t-PA treated patients in the 3-5 h time window had a SICH, compared to 5.3% in our cohort.…”
Section: Discussionsupporting
confidence: 84%
“…We found no difference in the occurrence of SICH and early in-hospital mortality between the sub-3 h and 3-4.5 h groups. We observed a similar incidence of SICH (5.7%) and early in-hospital mortality (9.7%) in thrombolysis up to 4.5 h as were reported in the NINDS study [1] and other t-PA registries [7,[12][13][14][15][16][17][18][19], where most patients were treated within 3 h. In the ATLANTIS trial [4], 7.0% of the t-PA treated patients in the 3-5 h time window had a SICH, compared to 5.3% in our cohort.…”
Section: Discussionsupporting
confidence: 84%
“…Only 9% to 22% of the patients receive intravenous thrombolysis. 19,17 In the present series 16.8% received intra-arterial thrombolysis. We must consider how to further increase the number of patients treated.…”
Section: Discussionmentioning
confidence: 57%
“…12,14,[17][18][19][20][21] It has also been shown that educational programs for both the public and physicians increase the number of patients arriving at the hospitals within the time limits for thrombolysis. 22 In US stroke centers, up to 59% of the patients who presented within 24 hours of symptom onset arrived within 3 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a post-hoc analysis concluded that patients treated within 3 hours appeared to benefit from rt-PA treatment. In fact, community studies have confirmed the safety and usefulness of the drug in routine clinical practice when administered within the first 3 hours after stroke symptom onset (2,30,74). Recently finished is the multinational Safe Implementation of Thrombolysis in Stroke Monitoring Study (SITS-MOST) which was designed to evaluate the safety and efficacy of IV rt-PA under routine clinical use when administered within 3 hours of symptom onset in acute ischemic stroke patients.…”
Section: Pharmacology Of Restoration Of Cerebral Perfusionmentioning
confidence: 99%